Some Pedagogical Technologies Used in the Process of Organizing Training Sessions in Higher Education Institutions (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
This article discusses the special emphasis is placed on the fact that any pedagogical technology applied to the process of training in higher education institutions, regardless of whether its components are passed through the content of the training, the textbook, the textbook or the activity of the pedagogue, should be aimed at developing the free and creative activity of the learner. Any lecture given at high volume will strain and tire the learners' hearing if it goes on for too long. That is why suggestions and recommendations are given on the organization of classes in the advanced pedagogical technologies.